SISTEM INFORMASI VAKSINASI PADA BALITA MENGGUNAKAN METODE WATERFALL - Kurniawan, Rudy; Artha, Emilya Ully; Wibowo, Fahrudin Mukti (Jurnal Komtika (Komputasi dan Informatika), 2019)
Mertoyudan Health Center is one of the public health service units located in Magelang Regency, Central Java Province. Data processing and vaccination scheduling for children under five years old at this Health Center are still not optimal. The developments in information technology have caused Mertoyudan Health Center start to develop information services using information technology. One of them is using a web-based information system. This research is conducted for building a web based data processing system and vaccination scheduling for children by implementing the Waterfall method. The results of black box testing on users can be obtained that the system which being built has fulfilled the needs of the Mertoyudan Health Center. The needs that has been met are toddlers data processing, scheduling and immunization for toddlers data reports. This system has become a solution for the availability of valid and transparent information for the immunization officers and The Head of this section at Mertoyudan Health Center.